Optical coherence tomography angiography of the macula and optic nerve head: microvascular density and test-retest repeatability in normal subjects - Lim, Ching Wei; Cheng, Jun; Tay, Elton Lik Tong; Teo, Hwei Yee; Wong, Elizabeth Poh Ying; Yong, Vernon Khet Yau; Lim, Boon Ang; Hee, Owen Kim; Wong, Hon Tym; Yip, Leonard Wei Leon (BMC ophthalmology, 2018)
Despite the potential usefulness of optical coherence tomography angiography in retinal and optic disc conditions, the reliability of the imaging modality remains unclear. This study set out to measure the microvascular density of macula and optic disc by mean of optical coherence tomography angiography and report the repeatability of the vessel density measurements. Cross sectional observational cohort study. Subjects with normal eyes were recruited. Two sets of optical coherence tomography angiography images of macula and optic nerve head were acquired during one visit. Novel in-house developed software was used to count the pixels in each images and to compute the microvessel density of the macula and optic disc. Data were analysed to determine the measurement repeatability. A total of 176 eyes from 88 consecutive normal subjects were recruited. For macular images, the mean vessel density at superficial retina, deep retina, outer retina and choriocapillaries segment was OD 0.113 and OS 0.111, OD 0.239 and OS 0.230, OD 0.179 and OS 0.164, OD 0.237 and OS 0.215 respectively. For optic disc images, mean vessel density at vitreoretinal interface, radial peripapillary capillary, superficial nerve head and disc segment at the level of choroid were OD 0.084 and OS 0.085, OD 0.140 and OS 0.138, OD 0.216 and OS 0.209, OD 0.227 and OS 0.236 respectively. The measurement repeatability tests showed that the coefficient of variation of macular scans, for right and left eyes, ranged from 6.4 to 31.1% and 5.3 to 59.4%. Likewise, the coefficient of variation of optic disc scans, for right and left eyes, ranged from 14.3 to 77.4% and 13.5 to 75.3%. Optical coherence tomography angiography is a useful modality to visualise the microvasculature plexus of macula and optic nerve head. The vessel density measurement of macular scan by mean of optical coherence tomography angiography demonstrated good repeatability. The optic disc scan, on the other hand, showed a higher coefficient of variation indicating a lower measurement repeatability than macular scan. Interpretation of optical coherence tomography angiography should take into account test-retest repeatability of the imaging system. National Healthcare Group Domain Specific Review Board ( NHG DSRB ) Singapore. DSRB Reference: 2015/00301.